Metallic species in yerba-mate and their infusions: Interrelationship of its distribution with phenolic compounds and melanoidins - Leoncio, Mariana Silva; da Cruz, Victor Hugo Maldonado; Saqueti, Bruno Henrique Figueiredo; de Castro, Matheus Campos; Silva, Amanda Maisa; Garcia, Edivaldo Egea; Frigo, Giovana; Ferreira, Carla Micaela Ripke; Friedrichsen, Jessica Souza; Santos, Oscar Oliveira (Seven Editora, 2023)
Yerba mate (Ilex paraguariensisis), also known as mate, is a plant traditionally cultivated and consumed in different South America countries, where its green or roasted, dry leaves are usually employed to prepare chimarrão or mate tea, respectively. Mate presents a very complex chemical composition, rich in bioactive compounds, including polyphenols and melanoidins, wich in turn can have several several health effects, mainly due to their antioxidant capacity and their role in the prevention of multiple diseases, such as cancer, diabetes, and cardiovascular diseases. In addition, mate also tends to accumulate essential and potentially toxic trace metals, and their presence in beverages prepared as infusion from the dried leaves of the plant may be influenced by factors associated with the preparation of those infusions. The extraction of metallic ionic species to the infusions it dependent of the nature of phenolic compounds and melanoidins present in mate, since this group of bioactive compounds are capable of associate with metal ions through complexation. This type of association can lead to the formation of compounds with different solubilities in aqueous media, consequently impacting the solubility of metal ions in the infusions. Moreover, the presence of different chemical forms of metal ions in infusions may influence their absorption by the human body. Thus, it is essential to carry out studies to evaluate and understand how the essential and potentially toxic trace elements present in yerba mate may be related to potential impacts caused by these minerals on the general health of consumers of its hot infusions. The present review aims to establish a connection between the chemical composition of yerba mate and the presence of metallic species in its infusions.DOI:https://doi.org/10.56238/globalhealthprespesc-061